THE SUNNI-SHI‘AH CONFLICT AND THE SEARCH FOR PEACE IN INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2013)
This article attempts to scrutinize the phenomenon of theological contestation in Indonesia, as represented by the Sunnite and Shi’ite conflict in the region of Sampang, East Java. The conflict has occurred due to Muslims’ inability to withstand the differences among them, so that violence is considered a way of final settlement. In this paper, the author will try, therefore, to analyze theological problems between the Sunnite and the Shi’ite in the region. It has been widely known that the Sunnite and the Shi’ite came out of the basis of similar truth, and, in fact, they share the same spirit of glorifying Islam around the world. In this way, all Muslim communities in the world, including the Sunnite and the Shi’ite, should be able to put their theological differences as God’s graces and the blessing of life, not as the point of conflict and disharmony.